2012
DOI: 10.1016/j.bbmt.2012.07.010
|View full text |Cite
|
Sign up to set email alerts
|

Effect of HLA-Matching Recipients to Donor Noninherited Maternal Antigens on Outcomes after Mismatched Umbilical Cord Blood Transplantation for Hematologic Malignancy

Abstract: Transplantation-related mortality (TRM) is high after HLA-mismatched umbilical cord blood (UCB) transplantation (UCBT). In utero, exposure to noninherited maternal antigen (NIMA) is recognized by the fetus, which induces Tregulator cells to that haplotype. It is plausible that UCBTs in which recipients are matched to donor NIMAs may alleviate some of the excess mortality associated with this treatment. To explore this concept, we used marginal matched-pair Cox regression analysis to compare outcomes in 48 NIMA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
45
0
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(51 citation statements)
references
References 24 publications
3
45
0
3
Order By: Relevance
“…Recent analyses have reported that inclusion of 4/6+1 NIMA matches triple the effectiveness of NIMA matching. 8,12 Although the availability of two (4/6+2 NIMA) and three (3/6+3 NIMA) NIMA matches were included in this analysis, their clinical relevance in CBT remains unclear. However, the positive results of 4/6+1 NIMA matching in unrelated CBT and 3/6+3 NIMA matching in haploidentical sibling HSCT and renal transplantation provide a rationale for including these in the BMDW NIMA Match Program to allow future clinical evaluation of these categories.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent analyses have reported that inclusion of 4/6+1 NIMA matches triple the effectiveness of NIMA matching. 8,12 Although the availability of two (4/6+2 NIMA) and three (3/6+3 NIMA) NIMA matches were included in this analysis, their clinical relevance in CBT remains unclear. However, the positive results of 4/6+1 NIMA matching in unrelated CBT and 3/6+3 NIMA matching in haploidentical sibling HSCT and renal transplantation provide a rationale for including these in the BMDW NIMA Match Program to allow future clinical evaluation of these categories.…”
Section: Discussionmentioning
confidence: 99%
“…A subsequent multicentre study confirmed the lower transplant-related mortality and improved survival associated with NIMA matching. 8 If a 4/6+1 NIMA match improves patient survival, it is also probable that a 4/6+2 NIMA match will provide similar or greater improvements, although studies have not yet analysed this hypothesis. Similarly, 3/6+3 NIMA matches may also be beneficial in CBT, particularly because in haploidentical sibling HSCT and renal transplantation, NIMA matches are associated with reduced acute GVHD and improved graft survival, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…It was hypothesized that recipients who are matched to donor NIMA may have lower mortality post transplantation. 5 year TRM was lower and OS was better among NIMA matched UCBT compared to NIMA mismatched UCBT (TRM 18% vs 32%, P = 0.05; OS 55% vs 38%, P = 0.04) [26] . It was suggested that NIMA matching can be considered in a patient with multiple UCB units harboring adequate cell dose.…”
Section: Ex Vivo T-cell Depleted Haploidentical Transplantationmentioning
confidence: 83%
“…Bu verilere dayanarak minimum çekirdekli hücre sayısını içeren kordon kanı ünitesi sağlandıktan sonra allel düzeyinde en uygun ünitenin seçilmesi gerekliliği vurgulanmıştır 46 . Uygun çekirdekli hücre sayısını içeren çok sayıda HLA uygunsuz kordon kanı ünitesi olması durumunda vericinin inherite edilmemiş maternal antijeninin(NIMA-non inherited maternal antigen) alıcının HLA'sı ile uyumunun transplanta bağlı mortaliteyi düşürdüğü gösterilmiştir 47 .…”
Section: Hla Uygunluğu Ve Hücre Sayısına Göre Kordon Kanı üNitesinin unclassified